Blockchain aware proxy re-encryption algorithm-based data sharing scheme - Keshta, Ismail; Aoudni, Yassine; Sandhu, Mukta; Singh, Abha; Xalikovich, Pardayev Abdunabi; Rizwan, Ali; Soni, Mukesh; Lalar, Sachin (Physical communication, 2023)
The blockchain stores transaction data in a distributed shared global ledger. It is challenging to strike a balance between privacy protection and usefulness while sharing data. Moreover, the dynamic adjustment of blockchain data access rights is a challenging problem. To this end, this paper suggests a blockchain data-controlled sharing scheme based on proxy re-encryption. First, a proxy re-encryption algorithm is constructed based on SM2 and the blockchain. Blockchain data sharing can give businesses a secure way to store and share data. Since this network is decentralized, and data is transmitted across a peer-to-peer network under the protection of an unchangeable cryptographic signature. Blockchain makes it more difficult to alter or hack the data. The data-controlled sharing scheme uses proxy re-encryption to protect transaction data privacy and realize data security sharing. Secondly, a dynamic adjustment mechanism for user rights is proposed. Blockchain nodes divide labor and manage re-encryption key parameters separately to achieve user access rights determinism Update, the visibility of transaction data is dynamically adjusted. Finally, the performance and security evaluation demonstrate that this scheme can realize the dynamic sharing of blockchain data while protecting transaction privacy and has advantages in computing overhead, which is better applicable to the Controlled sharing of blockchain data. This research suggests a regulated blockchain-based data-sharing system that makes use of proxy re-encryption. They are developing a proxy re-encryption algorithm with SM2 in order to fully safeguard the privacy of transaction data and to achieve data access authority determination by controlling proxy re-encryption key parameters. It is suggested to employ a hybrid attribute-based proxy re-encryption method that enables the proxy server to change attribute-encrypted cypher texts into identity-based encrypted cypher texts so that users with limited resources can access the previously encrypted material.